2020
DOI: 10.3390/molecules25235770
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Halogenated E-Stilbenols as Promising Antiaging Agents

Abstract: The increased risk of illness and disability is related to the age inevitable biological changes. Oxidative stress is a proposed mechanism for many age-related diseases. The crucial importance of polyphenol pharmacophore for aging process is largely described thanks to its effects on concentrations of reactive oxygen species. Resveratrol (3,5,4′-trihydroxy-trans-stilbene, RSV) plays a critical role in slowing the aging process but has a poor bioavailabity after oral intake. In this present work, a series of RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…However, the poor bioavailability and the high metabolic rate of RSV require the identification of new compounds with optimized structures. In previous studies, we have shown that the substitution of the 4-position on the aromatic ring of RSV with groups with different electronic and lipophilic properties improved their biological activity [35][36][37][38]. Most of the compounds studied here were tested for their antioxidant activity, and a correlation between the presence of 3 -chlorine and an improved scavenger ability of 4 -hydroxyl [38] was proven.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, the poor bioavailability and the high metabolic rate of RSV require the identification of new compounds with optimized structures. In previous studies, we have shown that the substitution of the 4-position on the aromatic ring of RSV with groups with different electronic and lipophilic properties improved their biological activity [35][36][37][38]. Most of the compounds studied here were tested for their antioxidant activity, and a correlation between the presence of 3 -chlorine and an improved scavenger ability of 4 -hydroxyl [38] was proven.…”
Section: Discussionmentioning
confidence: 64%
“…In previous studies, we have shown that the substitution of the 4-position on the aromatic ring of RSV with groups with different electronic and lipophilic properties improved their biological activity [35][36][37][38]. Most of the compounds studied here were tested for their antioxidant activity, and a correlation between the presence of 3 -chlorine and an improved scavenger ability of 4 -hydroxyl [38] was proven. Research conducted using HPLC showed that most of the compounds tested in this study had values of Log P higher than those of RSV [38].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…To enlarge the biological potential of RSV derivatives, and to ameliorate the pharmacokinetic profile, the hydroxy groups in the 3 and 5 positions were substituted with hydrogens and different functional groups were inserted in the 4'-position. These RSV derivatives with low molecular weight and better solubility were tested for their different bioactivities [49][50][51]. Starting from these premises, we herein surmise that the removal the 3,5-dihydroxy moiety and the anchoring a sulfonamide or sulfonate linker on the 4'-OH of RSV could improve its anticancer activity as well as chemical stability.…”
Section: Introductionmentioning
confidence: 94%